Policy-based Integration of Multi-Provider Digital Home Services - BRENNAN, ROB; KEENEY, JOHN; FEENEY, KEVIN CHEKOV; LEWIS, DAVID; O'SULLIVAN, DECLAN; ETZIONI, ZOHAR (My University, 2009)
The digital home is both the nexus of a new wave of user-centric service integration and the front line of competition between device vendors, connectivity providers, and added-value service providers. Vertical integration of provider offerings via bundled services and devices is no longer sufficient to satisfy customer demands for best of breed elemental services and services composed from traditional service provider offerings, networked consumer devices, Web applications, and social networks. New digital home services spanning these domains must mediate between highly dynamic and overlapping sources of configuration and execution authority, while respecting the desires of the customer and simplifying their interactions with the system. In this article we present a policy-based federated service management architecture that addresses these concerns for digital home devices participating in end-to-end communications services. We also describe an OSGi-based gateway prototype of the architecture and investigate the scalability of our approach via simulation.
PUBLISHED
Keywords: Federation; Policy-based Management; Computer Science